Photogrammetrical Assessment of Procedural Patterns and Sequential Structure in "Handaxe" Manufacture: A Case Study along the Doring River of South Africa. (2nd January 2017) - Bleed, Peter; Douglass, Matthew; Sumner, Alexandra; Behrendt, Maia; Mackay, Alex
ABSTRACT: When initially discovered in 2014, 21 Early Stone Age (ESA) pointed stone bifaces from the Uitspankraal 1 (UPK1) in western South Africa were left in the field but recorded for photogrammetry analysis. Digital models developed with these data made it possible to recognize that UPK1 handaxes were routinely produced with a process that emphasized outline rather than volumetric adjustment and usually involved only a single flip. The procedural uniformity of the assemblage is clear and rather easily accessible with the field-based photogrammetic technique.